A Médea és gyermekei az orosz irodalmi hagyomány tükrében - Goretity, József (Studia Litteraria, 2017)
The article approaches Lyudmila Ulitskaya’s Medea and Her Children from the Ancient Greek myth of Medea. The argument starts from the fact that despite the novel’s title, the text shows significant deviation from the story of the original myth. Likewise, the possible reasons for the remarkable differences between the Ancient Greek Medea figure and Ulitskaya’s eponymous heroine is the subject of investigation. It is argued that the differences are due to Ulitskaya’s distinct reliance on classical Russian literature besides the myth in creating her protagonist. The writer establishes intertextual links between her own novel and some outstanding works of Russian literature. As a result of such reminiscences and allusions, Ulitskaya’s heroine represents the moral values and an attitude to life much more typical of classical Russian literature than Antiquity. The article’s author concludes by highlighting that the success of Ulitskaya’s novels can be attributed to the writer’s excellence in combining postmodern literary techniques with the principles of “new realism” – a tendency that follows classical Russian literary traditions.